Seasonal droughts drive up carbon gain in a subtropical forest. (7th September 2022) - Njoroge, Brian; Li, Yuelin; Otieno, Dennis; Liu, Shizhong; Wei, Simin; Meng, Ze; Zhang, Qianmei; Zhang, Deqiang; Liu, Juxiu; Chu, Guowei; Haider, Fasih Ullah; Tenhunen, John
Abstract: The study aimed to show that droughts are increasing in frequency and intensity in the Dinghushan Biosphere Reserve and to illustrate the effects of seasonal droughts on carbon gain in a subtropical forest. This is in response to the threat posed by increased droughts due to global climate change. We used four drought indices to accurately determine periods of drought and periods of increased precipitation. Thereafter, the measured eddy flux and soil moisture content data collected from 2003 to 2014 were compared between the droughts and wet periods to determine drought impacts on the ecosystem carbon gain. Drought accounted for about 20% of the 12-year study period, with the highest drought events and severity occurring between 2012 and 2013. The average annual precipitation and air temperature during the study period were 1404.57 ± 43.2 mm and 22.65 ± 0.1 °C, respectively, showing a decrease of 523 mm in precipitation and an increase of 2.55 °C in temperature, compared with the 30-year records (1990–2020). Contrary to most published data for most forest ecosystems globally, Dinghushan Biosphere Reserve recorded significant carbon gain during 60% of the drought period. Graphical Abstract: